Segmental Resection of Mandible for Treatment Unicystic Ameloblastoma: a Case Report - Fadli Ashar; Eka Marwansyah; Andri Hardianto (Malahayati Nursing Journal, 2022)
ABSTRACT Ameloblastoma is the most common odontogenic tumour as it usually does not form metastasis, it is considered as benign tumour with a locally invasive growth pattern and destruction of the jaw and the surrounding tissue. Ameloblastoma annual incidence is 0.5 per 1.000.000 people, higher incidences are found in Africa, China and India in comparison with the western countries. About 80% of ameloblastomas are located in mandible, mainly in the third molar region, and 20% in the maxilla, particularly in the posterior region. Unicystic ameloblastoma is associated with a smaller relapse risk and is the only type that is susceptible for conservative surgery. Standar treatment for ameloblastoma today is radical resection with 1 cm resection margins. Recurrence range from 0 to 15% conservative surgery including enucleation and curettage recurrence rets as high as 55%. Recurrence ameloblastoma problem are associated with development of metastasis and transformation into ameloblastic carcinoma. Segmental resection with adequate margins followed by reconstruction with AO Plat the most ideal form of treatment available. Dentoalveolar rehabilitation is recommended in all such patients to improve final outcome. Keywords: Ameloblastoma, Segmental Resection, Reconstruction